SUSTAINABILITY OF WOMEN EMPOWERMENT THROUGH KUDUMBASHREE - Selvi. C, Saravana; Pushpa, K.S. (International Journal of Research -GRANTHAALAYAH, 2017)
Empowerment of women and their participation in the development process has been considered an essential feature of development. Gender equality and empowerment of women is recognized globally as a key element to achieve progress in all areas. Rural women are regarded as voiceless and defenseless. So they are to be empowered to fight against the evils faced by them1. Empowerment of women involves many things economic opportunity, social equality and personal rights. Women are deprived of their human rights, often as a matter of tradition. Kudumbashree plays a vital role in enhancing the financial status of the less privileged women in the State through its thrift and credit societies. These societies facilitate them to save and provide them with cost-effective and easy credit. The savings of the women are pooled together and given out as loans to the most deserving. The programme has 39.97 lakh members and covers more than 50% of the households in Kerala. Today, there are 2.58 lakhs NHGs, over 19,854 ADSs and 1,073 CDSs in Kudumbashree. A total of 100 Kudumbashree members were selected from Devikulam Block, Kerala by using random sampling method. The data was collected through interview schedule and a three point empowerment scale. The study revealed that more than half of the respondents 55 per cent acquired medium level of empowerment while high level is attained by 19 per cent and 26 per cent are in low level empowerment. Kudumbashree Neighbourhood groups (NHG) are considered as the dynamic tools of empowerment as it adopt a participatory approach for empowerment producing credible results since its inception till date. Empowerment of women through Kudumbashree will undoubtedly have long term socio-economic benefits. It could be concluded that the Kudumbashree programme could bring about radical changes in the lives of the poor sections of the society in the years to come.